LH increases the response to FSH in granulosa-lutein cells from sub/poor-responder patients in vitro. Issue 1 (11th November 2022) - Sperduti, Samantha; Paradiso, Elia; Anzivino, Claudia; Lazzaretti, Clara; Limoncella, Silvia; D'Alessandro, Sara; Roy, Neena; Reggianini, Francesca; Ferrari, Tommaso; Melli, Beatrice; La Sala, Giovanni Battista; Nicoli, Alessia; et al.
Abstract: STUDY QUESTION: Does LH addition to FSH in vitro recover the human primary granulosa lutein cell (hGLC) sub/poor-response? SUMMARY ANSWER: A picomolar concentration of LH may recover the FSH-induced cAMP and progesterone production of hGLC from sub/poor-responder women. WHAT is KNOWN ALREADY: Clinical studies suggested that FSH and LH co-treatment may be beneficial for the ovarian response of sub/poor-responders undergoing ovarian stimulation during ART. STUDY DESIGN, SIZE, DURATION: hGLC samples from 286 anonymous women undergoing oocyte retrieval for ART were collected from October 2017 to February 2021. PARTICIPANTS/MATERIALS, SETTING, METHODS: hGLCs from women undergoing ovarian stimulation during ART were blindly purified, cultured, genotyped and treated in vitro by increasing concentrations of FSH (nM) ±0.5 nM LH. cAMP and progesterone levels produced after 3 and 24 h, respectively, were measured. In vitro data were stratified a posteriori, according to the donors' ovarian response, into normo-, sub- and poor-responder groups and statistically compared. The effects of LH addition to FSH were compared with those obtained by FSH alone in all the groups as well. MAIN RESULTS AND THE ROLE of CHANCE: hGLCs from normo-responders were shown to have higher sensitivity to FSH treatment than sub-/poor-responders in vitro . Equimolar FSH concentrations induced higher cAMP (about 2.5- to 4.2-fold), and progesterone plateau levels (1.2- to 2.1-fold), in cells from normo-responder women than those from sub-/poor-responders (ANOVA; P  < 0.05). The addition of LH to the cell treatment significantly increased overall FSH efficacy, indicated by cAMP and progesterone levels, within all groups ( P  > 0.05). Interestingly, these in vitro endpoints, collected from the normo-responder group treated with FSH alone, were similar to those obtained in the sub-/poor-responder group under FSH + LH treatment. No different allele frequencies and FSH receptor ( FSHR ) gene expression levels between groups were found, excluding genetics of gonadotropin and their receptors as a factor linked to the normo-, sub- and poor-response. In conclusion, FSH elicits phenotype-specific ovarian lutein cell response. Most importantly, LH addition may fill the gap between cAMP and steroid production patterns between normo- and sub/poor-responders. LIMITATIONS, REASONS FOR CAUTION: Although the number of experimental replicates is overall high for an in vitro study, clinical trials are required to demonstrate if the endpoints evaluated herein reflect parameters of successful ART. hGLC retrieved after ovarian stimulation may not fully reproduce the response to hormones of granulosa cells from the antral follicular stage. WIDER IMPLICATIONS of THE FINDINGS: This in vitro assay may describe the individual response to personalize ART stimulation protocol, according to the normo-, sub- and poor-responder status . Moreover, this in vitro study supports the need to conduct optimally designed, randomized clinical trials exploring the personalized use of LH in assisted reproduction. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by Merck KGaA. M.L. and C.C. are employees of Merck KGaA or of the affiliate Merck Serono SpA. Other authors have no competing interests to declare. TRIAL REGISTRATION NUMBER: N/A.